2016
DOI: 10.1002/cphc.201600137
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Reversible Electronic Energy Transfer: From Molecular Dyads to Molecular Machines

Abstract: Reversible electronic energy transfer (REET) may be instilled in bi‐/multichromophoric molecule‐based systems, following photoexcitation, upon judicious structural integration of matched chromophores. This leads to a new set of photophysical properties for the ensemble, which can be fully characterized by steady‐state and time‐resolved spectroscopic methods. Herein, we take a comprehensive look at progress in the development of this type of supermolecule in the last five years, which has seen systems evolve fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…Electron donor‐acceptor linked multicomponent molecular dyads are considered as ideal platform for investigating and mimicking multistep charge separation process in photosynthesis . Tremendous efforts have been focused to develop multichromophoric systems (e. g. covalently tethered dyads or synthetic molecular machines) to establish reversible electronic energy transfer between the judicious designed and matched chromophores . However, the self‐assembly behaviors and functions of the assembled architecture of these multicomponent molecular dyads were rarely explored.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron donor‐acceptor linked multicomponent molecular dyads are considered as ideal platform for investigating and mimicking multistep charge separation process in photosynthesis . Tremendous efforts have been focused to develop multichromophoric systems (e. g. covalently tethered dyads or synthetic molecular machines) to establish reversible electronic energy transfer between the judicious designed and matched chromophores . However, the self‐assembly behaviors and functions of the assembled architecture of these multicomponent molecular dyads were rarely explored.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Tremendous efforts have been focused to develop multichromophoric systems (e. g. covalently tethered dyads or synthetic molecular machines) to establish reversible electronic energy transfer between the judicious designed and matched chromophores. [12] However, the self-assembly behaviors and functions of the assembled architecture of these multicomponent molecular dyads were rarely explored. Recently, we demonstrated that incorporating two kinds of chromophores in an extended and conjugated polymer scaffold could integrate or even amplify the photophysical properties of the individual ones.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25] These complexes were found to be appealing because of their easy structure elucidation by NMR, their compatibility with post-functionalisation methods and their 3 MLCT excited state, the lifetime and energy of which are suitable for water splitting [26][27][28][29] or charge separation processes. [30][31][32][33][34] However, the microsecond range excited state lifetime spanned by costly Ru II is not optimal for the design of technologically-adapted energy converting devices. The much cheaper Cr III N6 chromophores, which display long near infra-red (NIR) emission lifetimes that can reach the millisecond range in solution at room temperature, might be better suited for collecting and redistributing light-excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-chromophoric molecular systems, including covalently linked dyads and triads, attract much attention as models for experimental and theoretical studies of inter-chromophore interactions leading to excimer formation, [1][2][3][4][5][6] energy and/or electron transfer. [7][8][9][10][11][12][13][14][15][16][17][18] In the case when chromophores are also photochromes capable of reversibly photoisomerizing between two stable forms (isomers), multi-photochromic systems can serve as molecular digital switches and logic gates. [19][20][21][22][23][24][25] However, multi-photochromic systems, as compared with single photochromes, often undergo other (side) reactions, which limits possible applications of the former.…”
Section: Introductionmentioning
confidence: 99%